SEREN TAUN TRADITION in KASEPUHAN GIRIJAYA SUKABUMI - Lisda Triana; Andi (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2023)
The Indonesian nation is very rich in culture and traditions. One of the traditions it has is the Seren TaunTradition. Until now, this tradition is still preserved in several areas in West Jawa. This tradition is a tradition that has been carried out by the Sundanese people, by prioritizing one of the crops, namely rice. This tradition has been carried out in various areas of West Java, one of which is in Girijaya-Cidahu Village, Sukabumi, West Java. Even the agricultural sector is a source of livelihood for the people of Girijaya. Due to its strategic geographic location, which is near the mountains. In the era of globalization, it can be seen that many people have almost forgotten the traditions that surround them, but the Girijaya people have a strategy in preserving this Seren Taun Tradition, namely by means of local characters, palnting local chharacters to become a fortress to wirhstand the onslaught of outisde influences.